Changes in the anisotropic permeability of low-rank coal under varying effective stress in Fukang mining area, China. (15th December 2018) - Wang, Zhenzhi; Pan, Jienan; Hou, Quanlin; Niu, Qinghe; Tian, Jijun; Wang, Haichao; Fu, Xuehai
Highlights: A visualized fracture method was applied. The anisotropic characteristics of P-wave velocity and fractures were analyzed. Anisotropic permeability changes under the varying effective stresses were analyzed. The stress sensitivity coefficient parallel to the bedding plane is greater. The maximum irreversible permeability loss rate is perpendicular to the bedding plane. Abstract: Fractures are coalbed methane (CBM) migration pathways and key factors in determining coal reservoir permeability. During the depletion of CBM wells, the increase of effective stress with water pumping and gas desorption will affect gas production by changing reservoir permeability. However, the current understanding of the impacts of fracturing in different directions on CBM recovery is inadequate. In this work, we collected 4 types of cubic coal samples (samples cut parallel to face and butt cleats and perpendicular to the bedding plane) from the Fukang mining area in China to investigate the anisotropic characteristics of P-wave velocity, fractures and permeability under varying effective stresses from 3.5 to 8.5 MPa in the laboratory. The results indicate that the permeability exponentially decreased with increasing P-wave velocity. The acoustic wave velocities significantly decreased from direction perpendicular to the bedding plane to the butt cleat direction to the face cleat direction. However, the fracture aperture exhibited the opposite trend. The maximum acoustic wave velocities ratios of the perpendicular bedding plane direction to the parallel bedding plane direction are 1.12, 1.23, 1.05 and 1.15 for sample LY, DH, XG and QM, respectively. However, the ratios of butt cleat direction to face cleat direction are 1.23, 1.21, 1.01 and 1.07. A good coupling effect was detected between the aperture, porosity, connectivity, and permeability. The permeability decreased exponentially as the effective stress increased in the selected coal samples. Under the 3.5–6.5 MPa effective stress conditions, the permeability decreased rapidly, and from 6.5 to 8.5 MPa, the permeability decreased more slowly. Contrary to the permeability loss rate (PLR), the stress sensitivity coefficient and dimensionless permeability parallel to the bedding plane were greater than perpendicular to the bedding plane. The effective stress returned from 8.5 MPa to 3.5 MPa, and the permeability rebounded but did not fully recover. The irreversible permeability loss rate (IPLR) showed that the permeability was restored the least in the direction perpendicular to the bedding plane. The maximum IPLR ratios of the perpendicular to the bedding plane direction to the parallel bedding plane direction are 3.39, 5.34, 1.86 and 23.00 in sample LY, DH, XG and QM, respectively. According to the study of anisotropic fractures and permeability, multi-lateral well is recommended as the appropriate well type to obtain the optimal CBM recovery effect.